Longitudinal Intravital Imaging of the Retina Reveals Long-term Dynamics of Immune Infiltration and Its Effects on the Glial Network in Experimental Autoimmune Uveoretinitis, without Evident Signs of Neuronal Dysfunction in the Ganglion Cell Layer - Bremer, Daniel; Pache, Florence; Günther, Robert; Hornow, Jürgen; Andresen, Volker; Leben, Ruth; Mothes, Ronja; Zimmermann, Hanna; Brandt, Alexander U.; Paul, Friedemann; Hauser, Anja E.; Radbruch, Helena; et al. (Frontiers in Immunology, 2016)
A hallmark of autoimmune retinal inflammation is the infiltration of the retina with cells of the innate and adaptive immune system, leading to detachment of the retinal layers and even to complete loss of the retinal photoreceptor layer. As the only optical system in the organism, the eye enables non-invasive longitudinal imaging studies of these local autoimmune processes and of their effects on the target tissue. Moreover, as a window to the central nervous system (CNS), the eye also reflects general neuroinflammatory processes taking place at various sites within the CNS. Histological studies in murine neuroinflammatory models, such as experimental autoimmune uveoretinitis (EAU) and experimental autoimmune encephalomyelitis (EAE), indicate that immune infiltration is initialized by effector CD4+ T cells, with the innate compartment (neutrophils, macrophages and monocytes) contributing crucially to tissue degeneration that occurs at later phases of the disease. However, how the immune attack is orchestrated by various immune cell subsets in the retina and how the latter interact with the target tissue under in vivo conditions is still poorly understood. Our study addresses this gap with a novel approach for intravital two-photon microscopy, which enabled us to repeatedly track CD4+ T cells and LysM phagocytes during the entire course of EAU and to identify a specific radial infiltration pattern of these cells within the inflamed retina, starting from the optic nerve head. In contrast, highly motile CX3CR1+ cells display an opposite radial motility pattern, towards the optic nerve head. These inflammatory processes induce modifications of the microglial network towards an activated morphology, especially around the optic nerve head and main retinal blood vessels, but do not affect the neurons within the ganglion cell layer. Thanks to the new technology, non-invasive correlation of clinical scores of CNS-related pathologies with immune infiltrate behavior and subsequent tissue dysfunction is now possible. Hence, the new approach paves the way for deeper insights into the pathology of neuroinflammatory processes on a cellular basis, over the entire disease course.